MEKC-LIF method for analysis of amino acids after on-capillary derivatization by transverse diffusion of laminar flow profiles mixing of reactants for assessing developmental capacity of human embryos after in vitro fertilization - Celá, Andrea; Mádr, Aleš; Dědová, Tereza; Pelcová, Marta; Ješeta, Michal; Žáková, Jana; Crha, Igor; Glatz, Zdeněk (Electrophoresis, 2016)
Evaluating the physiological state of an organism is of clinical importance. In assisted reproduction, knowledge of the embryo's physiology is crucial for selecting the embryo with the highest developmental capacity to ensure high pregnancy rates. Amino acids (AAs) are involved in many biochemical processes during embryo development, which means that the determination of AA fluctuations in the embryo's surroundings can determine the embryo's physiological state. Since current embryo selection methods are mainly based on visual assessment, which lacks proper accuracy, a novel method for the analysis of AAs in the embryo's surroundings was developed. AAs were analyzed by means of MEKC-LIF after on-capillary derivatization by naphthalene-2,3-dicarboxaldehyde. The reactants were injected under the three zone arrangement and mixed using the transverse diffusion of laminar flow profiles methodology. The resulting derivatives of all the standard AAs were baseline resolved in the BGE comprised of 35 mM sodium tetraborate, 55 mM SDS, 2.7 M urea, 1 mM BIS-TRIS propane, and 23 mM NaOH within 50 min. The method was applied on an analysis of spent culture media used in assisted reproduction to culture embryos after in vitro fertilization.
Keywords: reprodukovatelnost výsledků; fertilizace in vitro; Reproducibility of Results; Humans; Chromatography, Micellar Electrokinetic Capillary; lidé; Naphthalenes; On-capillary derivatization; Embryonic Development; Amino acids; aminokyseliny; naftaleny; Amino Acids; Capillary electrophoresis; chromatografie micelární elektrokinetická kapilární; Transverse diffusion of laminar flow profiles; embryonální vývoj; Fertilization in Vitro; In vitro fertilization